Diastylis uniplicata sp. nov. (Crustacea: Cumacea: Diastylidae) a new Korean cumacean - Kim, Sung-Hyun; Lee, Chang-Mok (Zootaxa, 2021)
A new species of cumacean belonging to the genus Diastylis Say, 1818 was collected from the Nokdo Island, Korea. The new species, Diastylis uniplicata sp. nov., can be distinguished from all other Diastylis species by the combination of the smooth carapace surface with a transverse ridge and a pair of oblique ridges, and telson 1.7 times as long as pleonite 6, with 5–6 short stout simple setae laterally. Full illustrations of the new species, including the mouthparts, are given in this paper. Also, a key to the Korean species of Diastylis is provided.